Healing Trauma through Confession in Aristotelian Catharsis: a Discourse Analysis of Oscar Wilde’s De Profundis (1905) - Ibtissem Derrahi (International Journal of Social Communication, 2024)
This scientific study explores the cultural image of Algeria as portrayed in documentaries aired by Al Jazeera. Recognizing that documentaries aim to authentically represent reality through visuals and sound, this research falls within the category of descriptive studies. We employed a descriptive-analytical method, utilizing observation and content analysis tools, to focus on two documentaries: "The Chaoui Film" and "The Tuareg Film." These documentaries examine content related to Algerian cultural heritage and effectively convey an authentic and realistic image of Algeria's diverse customs, traditions, and cultural heritage. Additionally, they showcase various art forms, including traditional songs and local music, highlighting the unique cultural aspects of these regions.